Permagel/Permafrost: Lesbian desire and its translation - Iturregui-Gallardo, Gonzalo (Universidad de Antioquia, 2023)
Permafrost (Permagel in Catalan) is a novel by poet and writer Eva Baltasar. Published in 2018, it managed to gain notable popularity both in Catalonia and the rest of Spain. Since its publication, it has been translated into different languages with great success. Its English translation arrived in the UK in 2020 by American translator Julia Sanches. Baltasar’s story centres on a lesbian woman in her forties that, victim of the hostile environment in which she is obliged to live, fantasises about suicide and, at the same time, shows a hedonistic urge that leads her to the enjoyment of her human condition at its maximum, principally through sex. Sexual desire is explored in depth in the novel, unfolded very aesthetically in the author’s prose poetry. She manages to evoke images of strong symbolism and immediacy in a vast array of word combinations and metaphors. This article first explores the impact of the novel in both its original territory and among the English-speaking readership, particularly the topic of sex, which has a strong presence in the reviews. Secondly, it aims to analyse the description of lesbian (queer) desire in the original and its transfer into the English language through the lens of queer and feminist translation. By applying a queerfeminist perspective, the analysis describes the effectiveness of the translation when transporting the contents into another cultural and linguistic reality. Permafrost (Permagel en catalán) es una novela de la poeta y escritora Eva Baltasar. Publicada en 2018, la novela ganó notable popularidad tanto en Cataluña como en el resto de España. Desde su publicación, ha sido traducida a diferentes idiomas con gran éxito. Su traducción al inglés llegó al Reino Unido en 2020 de la mano de la traductora estadounidense Julia Sanches. La historia de Baltasar se centra en una mujer lesbiana en la cuarentena que, víctima del entorno hostil en el que se ve obligada a vivir, fantasea con el suicidio y, al mismo tiempo, muestra un impulso hedonista que la lleva a ...